A randomised controlled trial of pectoral nerve‐2 (PECS 2) block vs. serratus plane block for chronic pain after mastectomy. (19th September 2019) - Fujii, T.; Shibata, Y.; Akane, A.; Aoki, W.; Sekiguchi, A.; Takahashi, K.; Matsui, S.; Nishiwaki, K.
Summary: Thoracic interfascial plane blocks are effective for post‐mastectomy acute analgesia. However, their effects on chronic pain are uncertain. We randomly allocated 80 women equally to pectoral nerve‐2 (PECS 2) block or serratus plane block. The pectoral nerve‐2 block reduced the rate of moderate or severe chronic pain from 13/40 (33%) with the serratus plane block to 4/40 (10%), p = 0.03, adjusted odds ratio (95%CI) 0.23 (0.07–0.80), p = 0.02. The rates of pain‐free women at six postoperative months were indeterminate, 10/40 (25%) after serratus plane block vs. 19/40 (48%) after pectoral nerve‐2 block, p = 0.06, adjusted odds ratio (95%CI) 2.9 (1.1–7.5), p = 0.03. Health‐related quality of life at six postoperative months was similar after serratus plane and pectoral nerve‐2 blocks, mean (SD) EQ‐5D‐3L scores 0.87 (0.15) vs. 0.91 (0.14), respectively, p = 0.21. The pectoral nerve‐2 block reduced median (IQR [range]) morphine consumption in the first 24 postoperative hours from 6 (3–9 [1–25]) mg to 4 (2–7 [0–37]) mg, p = 0.04. However, acute pain scores after serratus plane and pectoral nerve‐2 blocks were similar, median (IQR [range]) 23 (11–35 [0–70]) mm vs. 18 (11–27 [0–61]) mm, respectively, p = 0.44. Pectoral nerve‐2 block reduced chronic pain 6 months after mastectomy compared with serratus plane block.